Escolha da especialidade médica: revisão integrativa da realidade nacional e o Instrumento SCIB - Caldeira, Renata Maria Ramos (2021)
Introduction: the choice of a medical specialty by Medicine students depends on several factors and can be a difficult task. Thus, counseling strategies must be investigated. In spite of that, Brazilian scientific literature has not given importance to this topic. Objective: analyze how the Brazilian medical education literature has dealt with the topic of choosing a medical specialty in the last decade. Moreover, the study aimed to introduce, as an initial and unprecedented experience at the national level, the SCIB (Special Choice Inventory - Brazil) questionnaire in medical schools in Minas Gerais so as to verify its acceptance and evaluate students' opinions regarding the use of this instrument as a facilitator in the choice of the medical specialty. Materials and Methods: the first stage consisted of conducting an integrative review of the national literature and the second one of an online application of the pre-SCIB, SCIB, and post- SCIB questionnaires to students in the last two years of medical courses in the state of Minas Gerais. Results: the 15 articles used in the review were divided and discussed within three thematic axes: Profile of the medical professional of a given specialty, Curricular Interventions, and Determinant factors in the choice of medical specialty. A low response rate to the SCIB questionnaire (n = 31) was found to be due to the limitations in recruitment strategies imposed by the COVID-19 pandemic and by the lack of knowledge about the importance of this type of tool. Conclusion: the process of choosing a medical specialty is multifactorial, continuous, and related to the self-knowledge of the future professional and the role of the tutor. The application of the SCIB questionnaire was well accepted by students and this initial and unprecedented experience should serve as a basis for further studies on the insertion of this questionnaire and other standardized tools in medical schools to support the process of choosing a medical specialty.